(untitled) (Eurasian Medical Research Periodical, 2023)
This article presents information on the treatment of degenerative-dystrophic diseases of the lumbar region of the spine with new diagnostic methods, analysis of positive results and study of their morphological basis. Taking into account the results of the morphological examination, the indications for carrying out optimal surgical procedures for degenerative-dystrophic diseases of the lumbar region of the spine have been determined. As a result of arcotomy + discectomy + foraminotomy examination, it was found that the pain syndrome was eliminated in all patients (100%). The advantage of hemilaminoectomy surgery is that the orthopedic properties of the spine are maximally preserved, the origin of instability is prevented, decompression of the spinal cord and brain roots is achieved, and congenital and acquired stenoses are opened. An extended hemylaminoectomy procedure maximizes stability of the spine and surrounding tissues, allowing immediate decompression and revision of the lobules and preserved brain roots